2019
DOI: 10.1017/s0954579419001391
|View full text |Cite
|
Sign up to set email alerts
|

The Young Adolescent Project: A longitudinal study of the effects of maltreatment on adolescent development

Abstract: The Young Adolescent Project (YAP) is an ongoing longitudinal study investigating the effects of abuse and neglect on adolescent development. It is a multidisciplinary study guided by a developmental, ecological perspective, and designed to consider the physical, social, and psychological effects of childhood maltreatment through the transition from childhood to adolescence. Four waves of data collection have been completed, ranging from early (Mean age = 10.95) to late adolescence (Mean age = 18.24). Members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…A limited number of studies have investigated multidimensional developmental competence in emerging adulthood with prospective samples of maltreated and nonmaltreated individuals (Allwood & Widom, 2013; DuMont, Widom, & Czaja, 2007; McGloin & Widom, 2001; Mersky & Topitzes, 2009; Negriff et al, 2019; Thornberry, Henry, Ireland, & Smith, 2010). 1 For instance, McGloin and Widom (2001) examined a large group of emerging adults (676 maltreated and 520 nonmaltreated, demographically similar comparison children) across eight domains of resilient functioning, defined as: successful employment, housing stability, high school graduation, social activity, absence of psychopathology, substance abuse, criminal offending, and violence perpetration.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have investigated multidimensional developmental competence in emerging adulthood with prospective samples of maltreated and nonmaltreated individuals (Allwood & Widom, 2013; DuMont, Widom, & Czaja, 2007; McGloin & Widom, 2001; Mersky & Topitzes, 2009; Negriff et al, 2019; Thornberry, Henry, Ireland, & Smith, 2010). 1 For instance, McGloin and Widom (2001) examined a large group of emerging adults (676 maltreated and 520 nonmaltreated, demographically similar comparison children) across eight domains of resilient functioning, defined as: successful employment, housing stability, high school graduation, social activity, absence of psychopathology, substance abuse, criminal offending, and violence perpetration.…”
Section: Introductionmentioning
confidence: 99%
“…All identified studies were unable to provide neurobiological evidence for the stress buffering role of friendship support in adolescents with CA (Table 1) [38,41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Negriff et al [42] found that 10-year-old adolescents with documented maltreatment experiences reported a smaller perceived friendship support network and showed blunted cortisol responses to social stress. At age 18, maltreated adolescents had more isolated online friendships (i.e., friends who were not connected to others in their online Facebook network), which predicted higher levels of exposure to online sexual content and offline highrisk sexual behavior [43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations